A case of progressively transformed germinal center-type IgG4-related lymphadenopathy. Issue 4 (August 2015) - Seki, Nobuhiko; Yamazaki, Norikazu; Koizumi, Jun-ichi; Takano, Ken-ichi; Abe, Ayumi; Ikeda, Tatsuru; Noguchi, Hiroko; Himi, Tetsuo
Abstract: Progressively transformed germinal centers (PTGC), a lymph node process unfamiliar to most otolaryngologists, is a morphological variant of reactive lymphofollicular hyperplasia of lymph nodes. Immunoglobulin (Ig)G4-related disease (IgG4-RD) is a newly identified condition, characterized by hyper-IgG4-γ-globulinemia and mass-forming or hypertrophic lesions associated with infiltration of IgG4 + plasma cells in the affected organs. Recently, a case study of PTGC was reported that fulfilled the diagnostic criteria of IgG4-RD (IgG4 + PTGC)[1] . A 68-year-old male was referred to our hospital with swelling in the left submandibular region. Palpation revealed swollen lymph nodes, the largest of which measured 5 cm in diameter. 18 F-fluorodeoxyglucose (FDG)-positron emission tomography/computed tomography identified lymphadenopathy with high 18 F-FDG uptake in the left submandibular region. We strongly suspected malignant lymphoma, and excisional biopsy of the submandibular lymph node was performed under general anesthesia. Pathological findings were consistent with IgG4 + PTGC, and serological examination demonstrated elevated levels of IgG4. These findings were consistent with IgG4-RD. The patient did not have systemic lesions; therefore, he has not undergone corticosteroid therapy. IgG4 + PTGC should be considered as a differential diagnosis for cervical lymphadenopathy by otolaryngologists as well as pathologists.